Complications of Laparoscopic Hysterectomy: Avoid the Risks - Carter, James E. (Hindawi Publishing Corporation, 1996)
Results of more than 1500 laparoscopic hysterectomies have been reported since 1989. The complication rate is 10 to 11% in expert hands. However, a complication rate of 60% was reported in one community hospital series. The risks of laparoscopic hysterectomy are acceptable at 10% but not at 60%. Practitioners of laparoscopic assisted vaginal hysterectomy must review and understand the risks associated with the procedure in order to avoid them. This article addresses the complications of laparoscopic hysterectomy and gives techniques to avoid them.